The Dutch Reformed Church Mission in Swaziland - A dream come true - Wyngaard, Arnau van (HTS teologiese studies, 2018)
This article covers the time from 1652 onwards when employees of the Dutch East India Company – most of whom were members of the Reformed Church in the Netherlands – arrived at the Cape of Good Hope in present South Africa. With time, a new church, the Dutch Reformed Church, was established in the Cape. In 1836, a number of pioneers moved from the Cape to the east of South Africa and some of them eventually made Swaziland their new home. Although most members of the white Dutch Reformed Church opposed any integration with Christians from other races, there was nevertheless a desire that they should join a Reformed Church. In 1922, the first Dutch Reformed congregation in Swaziland was established in Goedgegun in the southern region of the country, intended for the exclusive use of white, Afrikaans-speaking church members. In 1944, the first Reformed congregation for Swazi members was formed, which later became known as the Swaziland Reformed Church. This article documents the history of this church and concludes with a description of the Swaziland Reformed Church in 1985, with four missionaries from South Africa ministering in the four regions of Swaziland.